Prevalence and related factors of epilepsy in children and adolescents with cerebral palsy: a systematic review and meta-analysis - Gong, Chao; Liu, Annan; Lian, Beibei; Wu, Xixi; Zeng, Pei; Hao, Chaoli; Wang, Bobo; Jiang, Zhimei; Pang, Wei; Guo, Jin; Zhou, Shaobo (Frontiers in Pediatrics, 2023)
Objective: To study the worldwide prevalence and associated factors of epilepsy in children and adolescents with Cerebral Palsy (CP) and to analyze the differences between various subgroups.We identified all potential studies on the prevalence of epilepsy in children and adolescents with CP from PubMed, Web of Science, and Embase. The search time was from the establishment of the database to November 2022. Randomized effects meta-analysis models were used to calculate the prevalence of epilepsy in CP. Subgroup analysis and meta-regression were utilized to further explore heterogeneity between articles and prevalence disparities between subgroups. The funnel plot and Egger's test were used to investigate potential publication bias. Results: Seventy-two articles, comprising 53969 children and adolescents with CP, were included in this study. The results indicated a total epilepsy prevalence of 38.0% (95%CI: 34.8-41.2%) in CP. The prevalence of epilepsy was 46.4% (95%CI: 41.4-51.5%) in clinical sample-based studies and 31.6% (95%CI: 28.7-34.5%) in population-based studies. Meta-regression demonstrated that the sample source, neonatal seizure, family history of epilepsy, EEG or cranial imaging abnormalities, intellectual/cognitive impairment, and topographical types of CP were heterogeneous contributors to the epilepsy prevalence in CP.Approximately one-third of children and adolescents with CP have epilepsy, and the sample source can significantly impact the total prevalence of epilepsy. Neonatal seizures, family history of epilepsy, EEG abnormalities, cranial imaging abnormalities, severe intellectual disability, and quadriplegia may be contributing factors to epilepsy comorbid in CP. Further study is required to verify the strength of these associations with epilepsy. This study aids in identifying the clinical characteristics of young people with CP at risk of developing epilepsy, which may assist clinicians in the early prevention and diagnosis of epilepsy within this population.